Effects of axylitol-casein complex on insulin resistance and gut microbiota composition in high-fat-diet + streptozotocin-induced type 2 diabetes mellitus mice - Fanhua Kong; Juan Zhang; Shimo Kang; Xinyu Shen; Aicheng Liu; Yan Zheng; Junhua Shao; Xiqing Yue (Food Science and Human Wellness)
This study investigated the effects of a xylitol-casein non-covalent complex (XC) on parameters related to type 2 diabetes mellitus (T2DM), in addition to related changes in gut microbiome composition and functions. High-fat-diet (HFD) + streptozotocin (STZ)-induced T2DM mice were treated with xylitol (XY), casein (CN), and XC, after which fecal samples were collected for gut microbiota composition and diversity analyses based on 16S rRNA high-throughput sequencing and multivariate statistics. XC decreased body weight and improved glucose tolerance, insulin sensitivity, pancreas impairment, blood lipid levels, and liver function in T2DM mice compared to XY- and CN-treated mice. Furthermore, XC modulated the α-diversity, β-diversity and gut microbiota composition. Based on Spearman’s correlation analysis, the relative abundances of Alistipes, Bacteroides, and Faecalibaculum were positively correlated and those of Akkermansia, Lactobacillus, Bifi dobacterium, and Turicibacter were negatively correlated with the phenotypes related to the improvement of T2DM. In conclusion, we found that XC alleviated insulin resistance by restoring the gut microbiota of T2DM mice. Our results provide strong evidence for the beneficial effects of XC on T2DM and motivation for further investigation in animal models and, eventually, human trials.